Study of the Orthogonal Property of Recurrence Relations and the Differential Equation in Generalized Rodrigue's Formula - Raj Kishor Sharma (International Journal of Mathematics And its Applications, 2014)
Let $L_{1} =L_{1} (I)$ be the class of Lebesgue integrable functions on the interval $I=[a,b]$, where $0 \le a < b < ∞$ and let $Γ(.)$ be the gamma function.